HUMANISTIC CHARACTER EDUCATION CURRICULUM MODEL IN SDIT NURUL FIKRI ACEH BESAR - Husaini Husaini; Johansyah Johansyah (UIN Sumatera Utara Medan, 2019)
Character education is a system of planting character values to school citizens which includes the components of knowledge, awareness or willingness, and actions to implement these values, both to God Almighty, oneself, others, environment, and nationality so that we become human beings. In character education in schools, all components (stakeholders) must be involved, including the components of education itself, namely curriculum content, learning and assessment processes, quality of relationships, handling or management of subjects, school management, implementation of co-curricular activities or activities , empowering infrastructure, funding, and work ethics for all residents and the school environment. The focus of this research was the planning, implementation, and evaluation of humanistic character education curriculum. The approach of this research was a qualitative approach. The research model in accordance with this study was naturalistic phenomenology. For the determination of informants, purposive sampling technique was used. Research instruments or tools are the researchers themselves. The data collection of this study used four techniques, namely: in-depth interviews, participant observation, documentation studies, and triangulation. Data analysis uses steps namely; data reduction, data presentation, and data analysis